Rehabilitation in multiple sclerosis: Commentary on the recent AAN systematic review. Issue 6 (December 2016) - Sutliff, Matthew H.; Bennett, Susan E.; Bobryk, Patricia; Halper, June; Saslow, Lori A.; Skutnik, Lisa T.; Smith, Christine; Zackowski, Kathleen; Jones, David E.
Abstract : Multiple sclerosis (MS) is one of the most common causes of nontraumatic neurologic disability in young adults in the United States. Historically, MS care focused on rehabilitation and symptomatic management; however, this focus broadened with the development of disease-modifying therapies (DMTs), resulting in pharmacologic treatments that effectively reduce relapses and potentially slow the progression of disability. Consequently, DMTs often dominate many discussions regarding MS care, regardless of the fact that they do not reverse disability or restore function, arguably the primary goal of those with MS. Comprehensive, multidisciplinary care goes beyond the management of DMTs in MS treatment plans and strives to improve patient outcomes, functionality, and quality of life, goals that will likely prove to hold considerable importance as health care reimbursement transitions from a fee-for-service to a value-based paradigm. It is therefore likely that achieving improvement in some of the outcomes delineated in the American Academy of Neurology's (AAN) quality measures for MS will necessitate involvement of rehabilitation specialists. 1